2015
DOI: 10.1007/s12031-015-0571-0
|View full text |Cite
|
Sign up to set email alerts
|

Enriched Environment Altered Aberrant Hippocampal Neurogenesis and Improved Long-Term Consequences After Temporal Lobe Epilepsy in Adult Rats

Abstract: Abnormal hippocampal neurogenesis is thought to contribute to cognitive impairments in chronic temporal lobe epilepsy (TLE). Stromal cell-derived factor-1 (SDF-1) and its specific receptor CXCR4 play important roles in neurogenesis. We investigated whether enriched environment (EE) might be beneficial for TLE. Adult rats were randomly assigned as control rats, rats subjected to status epilepticus (SE), or post-SE rats treated with EE for 30 days. We used immunofluorescence staining to analyze the hippocampal n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 68 publications
2
8
0
Order By: Relevance
“…Morris water maze test. Spatial learning was analyzed with a match-to-place version of the Morris water maze test on days 31-33, as described previously (23). Following the assessment (day 33), a probe trial of 60 sec in the absence of the platform was performed to estimate the ability of the rats to recall the location of the platform by measuring the number of passings over its previous location.…”
Section: Methodsmentioning
confidence: 99%
“…Morris water maze test. Spatial learning was analyzed with a match-to-place version of the Morris water maze test on days 31-33, as described previously (23). Following the assessment (day 33), a probe trial of 60 sec in the absence of the platform was performed to estimate the ability of the rats to recall the location of the platform by measuring the number of passings over its previous location.…”
Section: Methodsmentioning
confidence: 99%
“…CXCL12 and its cognitive receptor CXCR4 are expressed by neural stem cells are involved in adult neurogenesis. 32 Enhanced environment induces neuronal plasticity and hippocampal neurogenesis which is accompanied by was accompanied by the increased expressions of SDF-1 and CXCR4 in the hippocampus, 33 indicating that CXCL12 is a neurogenesis inducer factor. This notion was supported by another observation which demonstrated that CXCR4 antagonist, AMD3100 reversed the effect of EE on neurogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . [ 27 ] reported the beneficial effects of using EE in rats having temporal lobe epilepsy. Their study revealed enhanced hippocampal neurogenesis, improved cognitive impairments, and decreased long-term seizure activity in epileptic rats after exposure to EE.…”
Section: Discussionmentioning
confidence: 99%